Student-centered leadership - Robinson, V. M. (Viviane M.) (San Francisco, CA. : Jossey-Bass, 2011)
'Busy school leaders need practical research-based guidance about effective educational leadership: the particular types of leadership practice that have the most pay-off in terms of improved academic and social learning of their students. This book clearly explains how leaders can create the conditions for improved teaching and learning in their schools. Expert author Viviane Robinson presents five dimensions of effective educational leadership. These five dimensions are clearly described, richly illustrated and their principles explained so that school leaders can intelligently adapt them for use in their own schools.'--
Includes bibliographical references (p. 157-166) and index.
Keywords: Educational leadership